2018
DOI: 10.1177/0284185118773541
|View full text |Cite
|
Sign up to set email alerts
|

Benign and malignant skull-involved lesions: discriminative value of conventional CT and MRI combined with diffusion-weighted MRI

Abstract: Background Little is known about the value of computed tomography (CT) and magnetic resonance imaging (MRI) combined with diffusion-weighted imaging (DWI) in distinguishing malignant from benign skull-involved lesions. Purpose To evaluate the discriminative value of DWI combined with conventional CT and MRI for differentiating between benign and malignant skull-involved lesions. Material and Methods CT and MRI findings of 58 patients with pathologically proven skull-involved lesions (43 benign and 15 malignant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…The nature of lesion can be lytic, sclerotic or mixed (lytic + sclerotic). The presence of lytic lesion represents aggressive nature of lesion and a sclerotic lesion may suggest a long standing lesion with remodelling [16]. In our study, CT detected lytic lesions in 15 cases, mixed lesions in 16 cases and sclerotic lesions in 5 cases whereas MRI detected lytic lesions in 17 cases, mixed lesions in 14 cases and sclerotic lesions in 6 cases.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…The nature of lesion can be lytic, sclerotic or mixed (lytic + sclerotic). The presence of lytic lesion represents aggressive nature of lesion and a sclerotic lesion may suggest a long standing lesion with remodelling [16]. In our study, CT detected lytic lesions in 15 cases, mixed lesions in 16 cases and sclerotic lesions in 5 cases whereas MRI detected lytic lesions in 17 cases, mixed lesions in 14 cases and sclerotic lesions in 6 cases.…”
Section: Discussionsupporting
confidence: 50%
“…2). Tu et al concluded that presence of cortical defects or break through or ill-defined lesion were important factors in differentiating benign and malignant lesions [16]. Another study conducted by Gomez et al, they concluded that benign lesions have well defined margins with a narrow zone of transition whereas malignant lesions have poorly defined margins with a wide zone of transition [17].…”
Section: Discussionmentioning
confidence: 99%
“…Biopsies are critical in establishing the diagnosis of SN‐NHL; however, magnetic resonance imaging (MRI), computed tomography (CT), and positron emission tomography (PET)/CT can determine the extent of the lesion as well as assist in early detection and ultimately establish disease staging 2,81 . Staging is used to determine pretreatment risk stratification and selection of therapy.…”
Section: Imagingmentioning
confidence: 99%
“…Biopsies are critical in establishing the diagnosis of SN‐NHL; however, magnetic resonance imaging (MRI), computed tomography (CT), and positron emission tomography (PET)/CT can determine the extent of the lesion as well as assist in early detection and ultimately establish disease staging. 2 , 81 Staging is used to determine pretreatment risk stratification and selection of therapy. CT best evaluates bony involvement and is typically the first imaging modality obtained; MRI aids in visualization of soft tissue; and PET/CT is recommended for extraprimary regional and distant spread.…”
Section: Imagingmentioning
confidence: 99%
See 1 more Smart Citation